The extraordinary education of Nicholas Benedict - Stewart, Trenton Lee. (Little, Brown, 2012)
Nine-year-old Nicholas Benedict, an orphan afflicted with an unfortunate nose and with narcolepsy, is sent to a new orphanage where he encounters vicious bullies, selfish adults, strange circumstances, and a mystery that could change his life forever.